EFFECTS OF ETHANOL EXTRACT OF LEILEM LEAVES (Clerodendrum minahassae) ON BLOOD GLUCOSE LEVELS OF MALE WHITE RATS - Lengkong, Cheisy Anastasya Gratia; Bodhi, Widdhi; Datu, Olvie Syenni; Fatimawali (UNIVERSITAS SAM RATULANGI, 2024)
Diabetes mellitus is a global chronic disease with more than 500 million patientes. Leilem leaf is an endemic plant of North Sulawesi from the genus Clerodendrum which is believed potentially antidiabetic. The purpose of this study was to determine the effect of ethanol extract of leilem leaf on blood glucose levels and body weight of male white rats. The extraction of leilem leaves using maceration method with 96% ethanol solvent. This study used the pretest posttest control group design method with 5 groups, namely group I positive control of metformin, group II negative control of 0.5% Na-CMC, group III, IV, and V were extract doses of 100, 200, and 400 mg/kgBW. All groups were induced with 120 mg/kg BW of alloxan. The results showed that leilem leaf extract had a significant effect (Asymp. Sig. (2-tailed) 0.001) on rats blood glucose levels with the best percentage in group V extract dose of 400 mg/kgBW and had no significant effect on body weight.